Strategic Policy Development for Flood Control in the Kambang Watershed of Jambi City Using SWOT–AHP Analysis - Jempater Agus Salim Sirait; Hutwan Syarifuddin; Fuad Muchlis (Rifa'Institute, 2026)
Introduction: Flooding is one of the major environmental challenges in Jambi City, particularly within the Kambang Watershed. High sedimentation rates, land-use changes, reduced drainage capacity, and rapid urban development have increased flood vulnerability in the area. Objective: This study aimed to identify the internal and external factors affecting flood control in the Kambang Watershed and to determine priority strategies for effective and sustainable flood management. Methods: The study employed an integrated Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and Analytical Hierarchy Process (AHP) approach. SWOT analysis was used to identify strategic factors influencing flood control, while AHP was applied to prioritize alternative strategies based on their relative importance. Results and Discussion: The results indicated that flood management in the Kambang Watershed is positioned in Quadrant II (Strength–Threat), suggesting that strong internal capacities can be utilized to address significant external threats. The proposed strategies include research and technology collaboration, implementation of sediment-control technology, enhancement of river normalization and rehabilitation programs, and integrated sediment management combined with river widening. The AHP results revealed that the implementation of sediment-control technology was the highest-priority strategy, with a weight of 0.46. Conclusion: Sediment control is the most critical strategy for reducing flood risk in the Kambang Watershed and should be supported by river rehabilitation programs, technological innovation, and stakeholder collaboration to achieve sustainable flood management while enhancing environmental health and public safety